Probabilistic model of divided conveyer belt to increase input performance of sorter feed systems - J. Föller (Logistics Research, 2016)
Maximization of input performance and throughput in sorting systems is a crucial interest of the industry. Due to self-impediment and mutual impediment at the input stage, a considerable reduction of throughput may occur. In this paper, a new design of a feeding system is discussed that addresses this deficiency, the divided conveyer belt (proposed by the author in 2003, patent DE 100 51 932 A). The new design is based on belt segments working at different, sequentially increasing speeds and takes into account ergonomic aspects to avoid worker fatigue. Based on a probabilistic model, that is the topic of this article, it will be argued that combined with sufficient spatial input variability the divided conveyer belt design substantially reduces the deficiency caused by mutual impediment and, consequently, increases input performance.
Keywords: 650; High-speed package sorter; Supply system (carrier); Feed system; Feeder; Input performance; Increasing throughput